Biblioteka Wydziałowa - Górna, Bożena; Zięba, Wioletta (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The contribution deals with departmental libraries at the Faculty of Law, the subsequent establishment of the Central Library for Law and its operation, with particular emphasis on availability of the resources to the readers. Over the decades of existence, The Library at the Faculty of Law has constantly enlarged its collections, thus becoming one of the biggest law libraries in Poland. Facing new technologies, the Library keeps up with the latest trends, as evidenced e.g. by setting up its own digital library and repository, or subscribing to various electronic databases. Not only do those developments contribute to the perception of the Library as a very modern institution, but they first and foremost facilitate the convenient and due access to legal and economic literature.
Keywords: Library of the Faculty of Law, Administration and Economics; University of Wrocław; history